2011
DOI: 10.1007/s11999-010-1645-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion of UHMWPE Particles Induces Increased Bone Macrophages and Osteolysis

Abstract: Background Aseptic loosening and periprosthetic osteolysis resulting from wear debris are major complications of total joint arthroplasty. Monocyte/macrophages are the key cells related to osteolysis at the bone-implant interface of joint arthroplasties. Whether the monocyte/macrophages found at the implant interface in the presence of polyethylene particles are locally or systemically derived is unknown. Questions/purposes We therefore asked (1) whether macrophages associated with polyethylene particle-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 39 publications
(59 reference statements)
4
85
0
Order By: Relevance
“…To confirm the specificity of the antiluciferase antibody, an identical staining protocol was repeated on control femora from a prior experiment from our laboratory, in which no cells were injected and either saline or UHMWPE was infused from the pump. 12 No luciferasepositive cell staining was seen in these sections.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 81%
See 4 more Smart Citations
“…To confirm the specificity of the antiluciferase antibody, an identical staining protocol was repeated on control femora from a prior experiment from our laboratory, in which no cells were injected and either saline or UHMWPE was infused from the pump. 12 No luciferasepositive cell staining was seen in these sections.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 81%
“…Additionally, previous work by Ren et al demonstrated that there was no increase in bioluminescence (reflecting systemic exogenous reporter cell trafficking) if reporter cells were not injected. 12 Injecting cells into a small, rapidly beating heart is more difficult than injecting cells into the tail vein, which is visible and remains still. We used the presence of blood in the syringe to indicate correct placement of the needle, but its placement throughout the duration of the injection is difficult to confirm.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations